Improving breaking efficiency of hard rock: Research on the mechanism of impact-shear rock breaking technology - Pei Ju; Dongzhuang Tian (Energy Exploration & Exploitation)
To expedite drilling operations in hard rock of coal mines, a new type of impact-shear drill bit was developed, and its mechanism of speed-up and efficiency increase was studied. The RHT constitutive model was used to describe the structural behavior of rock, and the rock-breaking simulation model of full-size bit was established. Compared with PDC bit and hammer bit, the rock-breaking force, bit torque, and rock stress characteristics of impact-shear bit were analyzed. The results show that, in comparison to PDC bit and hammer bit, the axial force of impact-shear bit was reduced by 68.25% and 71.40%, respectively, and the average torque was reduced by 91.79% and 83.36%, respectively. Notably, for the impact-shear bit, the fluctuation of drilling force was effectively mitigated, the stick–slip vibration of bit was weakened, the rock-breaking energy consumption was drastically reduced, and the rock-breaking efficiency and bit’s life were finally improved. In terms of rock stress characteristics, the pre-impact effect of the central hammer bit of the impact-shear bit can release the internal stress of the rock well, and the stress of the rock element on the hole wall was relatively reduced, thus making it easier for the external PDC bit to break the rock. Field test results show that, under the condition of the small drilling rig, the impact-shear bit can give full play to the pre-crushing function of the impact mechanism, thereby effectively protecting the PDC cutter of external PDC bit, and realizing the fast hole-forming in hard rock of coal mine.